Realne złożenie a realna różnica. Istota i istnienie w doktrynie św. Tomasza z Akwinu i Idziego Rzymianina - Kępa, Rafał (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2001)
The question about reality of the difference between existence and essence in creatures was one of the main problems of medieval metaphysics. The above text is an attempt to reconstruct two answers to this question: by Thomas Aquinas and Giles of Rome. Thomas Aquinas is a person most often associated with the problem of real difference. It seems, however, that the doctrine of Giles of Rome was also very important for the development of the problem. For example, Giles was the first to call the difference between existence and essence the "real difference". The doctrines of the two authors concerning real difference were often believed to be identical. However, beside some similarities, we can also find important differences between them. Aquinas appears to teach about real composition of existence and essence, while Giles writes about the real difference between the two, and he is so radical as to say that existence and essence are two different "things". In Giles' doctrine, we can also find clear Neo-Platonic influences. Giles puts special stress on accidental character of existence. This way he returns to Avicennian essentialism, discarded by St. Thomas.